Factors Impacting the Usage of E-Wallets in National Capital Region - Dr. Meenakshi Dhingra, Dr. Kanika Sachdeva, CMA Manisha Machan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
There has been a noticeable spike in cashless transactions in recent years due to the advancements of financial technologies, new government initiatives and the nationwide unprecedented situation. Taking the mentioned circumstances into consideration, the current research is carried out to identify the various factors encouraging the people to use the e-wallets. Moreover, this research addresses the various purposes for which people use e-wallets and the major challenges they face while using the services of e-wallets. The primary data were collected from 285 respondents belonging to National Capital Region (NCR) of India. Out of the total respondents, 221 use e-wallets and 64 were non users. The collected data were analysed using multiple statistical tools including descriptive statistics, shapiro-wilk test of normality and Garrett rank analysis. The outcomes of the study highlighted that the facility of using e-wallets from anywhere is the most appealing reason for adopting the use of e-wallets and it is not at all treated as status symbol for the individuals, therefore status symbol has no role in determining the use of e-wallet. It is also found that the e-wallets are most preferred for mobile recharge, however it is least preferred for toll payments and fuel charges. Moreover, the study has stressed upon the fact that the frauds that happen with most of the people is the key issue that the individuals have regarding usage of e-wallets. Furthermore, the analysis conducted on the 64 non-users of e-wallets highlighted that the main reasons for not using e-wallets were their habits of making cash payments and security concerns. The outcome of this study has multiple implications for the upliftment and enhancement of e-wallet services in India. Therefore, this study offers few suggestions based on the results for the development of e-wallet service providers in the coming years.